A Novel Quantitative Method for Analyzing Desmopressin in Human Plasma Using Liquid Chromatography–Tandem Mass Spectrometry. Issue 6 (December 2020) - de Jager, Nico C. B.; Heijdra, Jessica M.; Pistorius, Marcel; Kruip, Marieke J. H. A.; Leebeek, Frank W. G.; Cnossen, Marjon H.; Mathôt, Ron A. A.
Abstract : Background: Desmopressin (D-amino D-arginine vasopressin: dDAVP) is used for the treatment of patients with hemophilia A and Von Willebrand disease. Studies on the rationale of dosing are scarce and mainly focus on the underlying causes of the vast differences in desmopressin response among individuals. The aim of this study was to develop and validate a liquid chromatography–tandem mass spectrometry (LC-MS/MS) method for the quantification of desmopressin in human plasma for identifying its pharmacokinetics and its therapeutic effect relationship in patients with bleeding disorder. Methods: The method entails solid-phase extraction with ion exchange for sample clean-up, followed by an LC-MS/MS run. The technique has been validated for analytical selectivity as well as specificity, process efficiency, linearity, accuracy, imprecision, and stability. Results: This method showed good selectivity because no significant chromatographic matrix interferences were observed. The determination coefficient ( R 2 ) of the calibration curves was ≥0.990. Analyte accuracy ranged from 89.2% to 111.8%, and the between- and within-run imprecision was less than 9.3% in a plasma concentration and range from 60 to 3200 pg/mL. Samples were stable during 3 freeze/thaw cycles with an additional 120 hours of storage at room temperature (21°C–24°C) and 96 hours in the autosampler (10°C). The total run time was approximately 5 minutes. Conclusions: The LC-MS/MS method presented enables quantification of desmopressin in human plasma, and it is sensitive, specific, efficient, accurate, and precise. This analytical technique is a valuable and useful tool to study the interpatient variability of pharmacokinetics. Abstract : Supplemental Digital Content is Available in the Text.